Effect of COVID-19-Related Interventions on the Incidence of Infectious Eye Diseases: Analysis of Nationwide Infectious Disease Incidence Monitoring Data - Woo-Ri Lee; Li-Hyun Kim; Gyeong-Min Lee; Jooyoung Cheon; Young Dae Kwon; Jin-Won Noh; Ki-Bong Yoo (International Journal of Public Health, 2022)
Objective: Social distancing has been confirmed to reduce the incidence of not only the COVID-19, but also the incidence of other diseases. Therefore, this study aimed to investigate the effect of social distancing policies on the incidence of infectious eye diseases by monitoring their nationwide incidence data in all age groups.Methods: In this study, to analyse the impact of COVID-19 policy on IEDSC, the time periods were divided into two interventions. The first intervention was the first COVID-19 patient report in Korea on 19 January 2020. The second intervention was relaxation of the social distancing policy on 6 May 2020. Segmented regression analysis of the interrupted time series was used to assess COVID-19 policies on the IEDSC.Results: After the first incidence of a COVID-19 patient, IEDSCs decreased significantly in all age groups, while the relaxation of the social distancing policy increased IEDSCs significantly, mostly in all groups.Conclusion: In the post-COVID-19 era, we hope that national-level interventions such as reducing air pollution and employing precautionary measures will significantly reduce the financial burden of developing infectious ophthalmic diseases.